Some characteristics of the Sudanese bread (Kisra) supplement with fenugreek (Trigonella foenum-graecum L) - E. Suliman, Abdel Moneim; O. Ali, Ali; A. Elkhalij, Elamin (Gezira Journal of Agricultural Science; Vol 1 No 2 (2003), 2021)
In this study the chemical composition of two fenugreek seed types known locally as Sudanese and Ethiopian' types and sorghum kisras supplemented with 5%, 10% and 20% flour of the two fenugreek types after removal of the bitter taste, was determined* The two fenugreek seed types had shown slightly small differences in most of their chemical components, however, the Ethiopian type had slightly more protein (26.4+0.4 %) than that of the Sudanese type (25.5± 0.07 %). On the other hand, the Sudanese type contained more mucilage (23.5±0.04 %) than that of the Ethiopian type (22.6±0.010/0). The most significant effect of kisra supplementation was the increase in good quality protein by a range of 31-66%. It increased from 11.20% in the control kisra to the range of 14.70-18.64%. The crude fibre% of the control kisra (3.40%) increased in the supplemented kisras to the range of 4.54-5.30%. The ash% decreased from 2.42% in the control kisra, to the range of 2.20 - le20% in the supplemented kisras. The sensory analysis indicated that the fenugreek supplemented kisra was accepted by the panelists at the 5% level of fenugreek seed flour supplementation. The overall acceptance level of the different samples decreased with the increase in fenugreek seed flour used in supplementation.